Reconfigurable self-assembly of photocatalytic magnetic microrobots for water purification - Mario Urso; Martina Ussia; Xia Peng; Cagatay M. Oral; Martin Pumera (Nature Communications, 2023)
Abstract The development of artificial small-scale robotic swarms with nature-mimicking collective behaviors represents the frontier of research in robotics. While microrobot swarming under magnetic manipulation has been extensively explored, light-induced self-organization of micro- and nanorobots is still challenging. This study demonstrates the interaction-controlled, reconfigurable, reversible, and active self-assembly of TiO2/α-Fe2O3 microrobots, consisting of peanut-shaped α-Fe2O3 (hematite) microparticles synthesized by a hydrothermal method and covered with a thin layer of TiO2 by atomic layer deposition (ALD). Due to their photocatalytic and ferromagnetic properties, microrobots autonomously move in water under light irradiation, while a magnetic field precisely controls their direction. In the presence of H2O2 fuel, concentration gradients around the illuminated microrobots result in mutual attraction by phoretic interactions, inducing their spontaneous organization into self-propelled clusters. In the dark, clusters reversibly reconfigure into microchains where microrobots are aligned due to magnetic dipole-dipole interactions. Microrobots’ active motion and photocatalytic properties were investigated for water remediation from pesticides, obtaining the rapid degradation of the extensively used, persistent, and hazardous herbicide 2,4-Dichlorophenoxyacetic acid (2,4D). This study potentially impacts the realization of future intelligent adaptive metamachines and the application of light-powered self-propelled micro- and nanomotors toward the degradation of persistent organic pollutants (POPs) or micro- and nanoplastics.